Hybrid Solar-MILD Combustion for Renewable Energy Generation - Chinnici, Alfonso; Nathan, Graham J.; Dally, Bassam B. (Frontiers in Mechanical Engineering, 2019)
The intermittent nature of solar energy limits its further deployment to applications where firm supply and constant output is required. While energy storage is a viable option to increase solar share, in itself is not sufficient without an additional dispatchable energy source. Combustion of both fossil-based and renewable fuels can provide the demand ready energy source required and lends itself to hybridisation with tower based Concentrated Solar Thermal, CST, energy. The Hybrid Solar Receiver Combustor, HSRC, is a novel technology that integrates both sources of energy in one device and offers tangible benefits in increased solar share, thermal efficiency and reduced capital and operation costs. This paper reports a brief review of the different findings from experimental and computational research carried out at the Centre for Energy Technology of the University of Adelaide into optimizing the HSRC design, developing the first-of-a-kind laboratory-scale HSRC unit and evaluating its performance under different fuels, operating conditions and modes of operation. It highlights the benefits and need for utilizing MILD combustion in the HSRC to match the heat transfer characteristics and stability required to achieve similar operational range and efficiency from both sources of energy. A 5-kWel xenon-arc solar simulator and the combustion of a wide variety of fuels are used as the energy sources. This paper reports on the effectiveness of MILD combustion under these conditions and in particular it discusses flame stability envelop and its relation to heat extraction, temperature and pollutant emissions. It also reports on thermal efficiency, heat losses and heat flux distribution within the cavity for all fuels and operating conditions. It is found that the HSRC thermal performance is similar under the three operation modes (solar, combustion and combined) and that operating under MILD combustion mode allowed fuel flexibility, homogeneous heat distribution and very low emission of NOx and CO. Also found that H/C ratio plays a minor role in the radiated energy to the heat exchanger within the cavity. Future research and further technology development need is also discussed in this paper.